2006
DOI: 10.1016/j.icesjms.2005.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Otolith chemistry: an aid to stock separation of Helicolenus dactylopterus (bluemouth) and Merluccius merluccius (European hake) in the Northeast Atlantic and Mediterranean

Abstract: Helicolenus dactylopterus and Merluccius merluccius are widely distributed on the continental slopes of the Atlantic and Mediterranean and have quite different life histories. Both are commercially exploited, but little is known about their stock structure. Fish otolith composition is thought to reflect both endogenous processes and external factors, some of which relate to the surrounding environment, and therefore may be used as a tool for stock discrimination. The elemental composition of sagittal otoliths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 39 publications
4
44
1
Order By: Relevance
“…Mg is one of the most important elements in otoliths separating fish from deepwater areas. Swan et al (2006) found that Mg along with Pb were important for differentiating deep water fish stocks of the European hake, Merluccius merluccius, in the northeastern Atlantic. The otolith chemistry results were consistent with the treatment of a northern stock west of Norway and a southern stock off Portugal that were separated by an oceanographic and bathymetric feature, the Bay of Biscay.…”
Section: Discussionmentioning
confidence: 95%
“…Mg is one of the most important elements in otoliths separating fish from deepwater areas. Swan et al (2006) found that Mg along with Pb were important for differentiating deep water fish stocks of the European hake, Merluccius merluccius, in the northeastern Atlantic. The otolith chemistry results were consistent with the treatment of a northern stock west of Norway and a southern stock off Portugal that were separated by an oceanographic and bathymetric feature, the Bay of Biscay.…”
Section: Discussionmentioning
confidence: 95%
“…It is of fundamental importance to address this issue for improvement of stock assessments and for common stock management, because these estuarine environments are significant nursery areas for several highly commercial species intensively fished within the European Union. In recent years, research has been focused mainly on stock discrimination or natal origin of marine species in the North Eastern Atlantic, Mediterranean and North seas (Rooker et al 2003, Swan et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…The value of Mg, Mn, and Cu for identification of fish habitat by otolith fingerprints has already been acknowledged (e.g. Swan et al 2006, Clarke et al 2009, Tanner et al 2011, although the exact roles played by physiological effects, bioavailability, and water temperature in defining their final otolith concentrations remain unclear (Tanner et al 2011). In our case, the spatial differences in otolith concentrations observed largely reflect differences in physicochemical conditions and element bioavailability between the 4 habitats, under the combined influence of Rhône River inputs to the marine coastal zone and the Thau and Mauguio lagoons (Accornero et al 2008, Ollivier et al 2011, minor localized pollutions by Cu and Cr in the Salses-Leucate lagoon (IFREMER 2009), and differences in water temperature and salinity between the lagoons and the sea (Cacho et al 1999, IFREMER 2008.…”
Section: Methodological Limitations and Usefulness Of Multi-elementalmentioning
confidence: 99%